MEDIASI SEBAGAI UPAYA PENYELESAIAN MASALAH ANTARA PT ANEKA SUMBERBUMI JAYA DENGAN WARGA DESA BUMISARI KECAMATAN NATAR LAMPUNG SELATAN - Aprilia Rahmawati; Muher Sukmayanto; Helvi Yanfika (Universitas Galuh Ciamis, 2019)
This study analyzes: (1) the implementation of mediation as a method of resolving problems that occur between PT Aneka Sumberbumi Jaya and Residents of Bumisari Village, Natar Subdistrict, South Lampung (2) obstacles in conducting mediation as a method of resolving problems that occur between PT Aneka Sumberbumi Jaya and Bumisari Village Residents Natar District, South Lampung. This research was conducted in Bumisari Village, Natar District, South Lampung. The selection of research locations was done purposively. The informants from this study consisted of the Head of the mine who was a representative of the company, representatives of the residents of Bumisari Village, the village head and representatives of the Natar Police Sector as a mediator. The method used in this research is descriptive method with the data used are primary data and secondary data. The results showed that: (1) The mediation process carried out by PT Aneka Sumberbumi Jaya and Bumisari villagers proceeded well with 6 stages, namely the delivery of the wishes of the disputing parties, description of the situation and case identification, problem mapping, resulting settlement alternatives disputes, alternative evaluations and elections and formulating agreements (2) Obstacles in the mediation between PT Aneka Sumberbumi Jaya and Bumisari Village residents are the lack of awareness of the company in carrying out the rights and obligations that must be carried out to the community. Another obstacle is the selfish attitude of each party in dispute that causes problem solving to take place in a rigid and convoluted manner that takes a long time.